PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) TERHADAP TANGGUNG JAWAB DAN KERJA KERAS SISWA - Triwoelandari, Retno; Fadilah, Afiyanti (Program Studi PGMI, 2015)
This research aimed to know what kinds of characters found before applying model of cooperative learning type numbered heads together (NHT) and how is the effect of that model to responsibility and hard work students. The research conducted qualitative. Based on the data, the research found that majority of character found before applying the model was discipline (57 %) and awareness (61 %), but both characters are less enthusiasm. In contrast with class IV B, the character found are curiosity (59 %), responsibility (36 %). This model increases students’ responsibility in class IV A from 41 % to 81 %, and hard work’s from 45 % to 71 %. The increasing both character are also found in IV, the responsibility from 41 % to 51 %, hard work from 36 % to 45 %. In conclusion, this research has a significance for the teacher to conduct a model of cooperative learning type numbered heads together (NHT) in teaching learning process.